2006
DOI: 10.1002/hlca.200690028
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Dimers of Some 2‐Substituted Indan‐1‐one Derivatives during Base‐Mediated Cross‐Aldol Condensation

Abstract: Unexpected dimers of some 2‐substituted indan‐1‐one derivatives were isolated during aldol condensation of indan‐1‐one with various aldehydes in the presence of KOH (see Scheme). Monomeric products, usually expected from aldol condensation, further underwent a base‐catalyzed nucleophilic addition reaction to their dimeric form in some cases. The structures of these dimers were characterized by using various spectral techniques and in one case, structural details were determined from a high‐resolution crystallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Substituted aldehydes (wherever not commercially available) were prepared by alkylating the aldehydes with requisite halogenated derivative in ethyl methyl ketone in the presence of anhydrous potassium carbonate. Previously we have reported the formation of dimers during base mediated aldol condensation of indan-1-one with various aldehydes (Narang et al, 2006;Gupta et al, 2004). It was observed that presence of an electron withdrawing para substituent and electron donating meta substituent facilitates the dimer formation.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Substituted aldehydes (wherever not commercially available) were prepared by alkylating the aldehydes with requisite halogenated derivative in ethyl methyl ketone in the presence of anhydrous potassium carbonate. Previously we have reported the formation of dimers during base mediated aldol condensation of indan-1-one with various aldehydes (Narang et al, 2006;Gupta et al, 2004). It was observed that presence of an electron withdrawing para substituent and electron donating meta substituent facilitates the dimer formation.…”
Section: Chemistrymentioning
confidence: 99%
“…As a part of our ongoing research program pertaining to the synthesis of monomeric and dimeric 2-benzylidene indanones as potent aromatase inhibitors (Narang et al, 2006;Gupta et al, 2004), we now report the aromatase inhibitory activity of a new series of imidazolyl-substituted indanone derivatives. This study encompasses the synthesis of a new series of indanone derivatives by base mediated aldol condensation of indan-1-one with various substituted aldehydes and their evaluation for inhibitory activity towards aromatase enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…After the solvent removed in vacua, the product was crystalized with EtOH. The structures of 4a-h were determined by spectroscopic studies ( 1 H-, 13 C-, 2D-NMR and IR) and literature data [18]. The relative stereochemistry of 4a was established by COSY, HETCOR, HMBC and NOESY experiments, which confirmed the relative configuration between all the neighboring substituents (Figure 2, Figure 3 and Figure 4).…”
Section: General Procedures For the Synthesis Of 13-diaryl-133a8a-tetrahydro-8hspiro[cyclopenta[a]indene-22'-indene]-1'8(3'h)-dione (4a-hmentioning
confidence: 80%
“…1 H and 13 C NMR spectra were recorded on a Bruker Avance DPX-400 instrument and Agilent 600 MHz Premium COMPACT NMR instrument in CDCl3 (for 4bh) and DMSO-d6 (for 4a); δ in ppm rel. to Me4Si (δ 0.00) for 1 H NMR, CDCl3 (δ 77.0) and DMSO-d6 (δ 39.5) for 13 C-NMR spectra as internal standards, J in Hz. NOESY spectra of 4a was recorded on Bruker 300 Mhz Ultrashield instrument in DMSO-d6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation